Analisis dan Simulasi Shell Heavy Oil Fractionator (SHOF) Menggunakan Metode Kontrol PID - Aria EL, Jusagemal; Setiawan, Iwan; Setiyono, Budi (Transmisi, 2011)
Shell Heavy Oil Fractionator (SHOF), types of distillation columns are often used as models in the application of advanced control, are examples that illustrate the dynamics of real plant from the process industries, especially petroleum refining industry. This thesis research analysis and simulation of control systems Shell Heavy Oil Fractionator column (SHOF) which is a multivariable system with three inputs and three outputs (Multi Input Multi Output). Interaction between subsystems is reduced by applying the method of Relative Gain Array and decoupling, so the system can be transformed into three Single Input Single Output (SISO). Control system uses Proportional Integral control (PI) and Proportional Integral Derivative control (PID). SHOF control system simulation can be concluded that decoupling eliminate the influence of input Top Draw on outputs Side End Point Composition and Bottom Reflux Temperature, influence of input Side Draw on outputs Top End Point Composition and Bottom Reflux Temperature, as well as the influence of inputs Bottom Reflux Duty on outputs Top End Point Composition and Side End Point Composition. The best results were obtained from the Top End Point Composition control using PID control Chien-Regulator 1, Side End Point Composition using PI control Minimum IAE-Murill Regulators, and the Bottom Reflux Temperature using PI control with closed loop time constant (Tcl) for 1.5 minutes. Keyword : Shell Heavy Oil Fractionator (SHOF), Relative Gain Array (RGA), decoupling, PID control